(untitled) - Prof. Dr. Volker Amelung (Medizinische Hochschule Hannover); Dr. Bernadette Klapper (Leitung der Forschungsstelle Pflegeversicherung, GKV-Spitzenverband, Berlin); Franz Knieps (ehem. Vorstand des BKK Dachverbandes e.V., Berlin) (Gesundheits- und Sozialpolitik (G&S), 2025)
Gesundheits- und Sozialpolitik is an independent journal that informs about new developments in legislature and management regarding healthcare and social security. Insiders and scholars discuss recent reforms, rehash background information, develop case scenarios for legislature, describe ways and conflicts of management, and document jurisdiction in a comprised form. The journal addresses corporations of all industries, human resources managers, organizations, administration bureaus, unions, and works committees. Website: www.gus.nomos.de